Tornado loss model of Oklahoma and Kansas, United States, based on the historical tornado data and Monte Carlo simulation. (February 2020) - Refan, Maryam; Romanic, Djordje; Parvu, Dan; Michel, Gero
Abstract: This paper introduces a new tornado loss assessment model for one-family and two-family wood frame residential buildings in the states of Kansas (KS) and Oklahoma (OK), United States. The model belongs to the group of Monte Carlo simulations and consists of five main modules: (1) tornado climatology; (2) tornado intensity and tornado track geometry; (3) exposure map; (4) fragility and vulnerability functions; and (5) financial module that is used to calculate the resulting damages. In addition, two analytical formulations of radial distribution of tangential velocity in tornado vortex were implemented in the tornado intensity module—Rankine Vortex (RV) and Modified Rankine Vortex (MRV) models. Using the MRV tornado model, the resulting mean aggregated annual expected losses for the return period of 1000 years are US 392, 080, 526.8 and US 641, 281, 336.0 for KS and OK, respectively. Although house prices in KS are higher than in OK, the higher occurrence of tornadoes in OK combined with the larger population of OK (i.e., larger density of houses) result in the increased tornado losses for OK. The losses derived using the MRV module are higher than the losses from the RV module due to the RV module underestimating the tornado tangential velocity. Furthermore, the losses predicted by the current model using the MRV formulation are less than the estimated losses from the previous version of the model (Romanic et al., 2016). The model is also tested for the case of a single tornado track positioned over suburban area of Oklahoma City, OK.